Analysis of Land Subsidence in Peatlands in the Awareness Area of Pekanbaru, Riau, Indonesia - Husnul Kausarian; Windi Indra Sari; Fitri Mairizki; Batara Batara; Adi Suryadi (Journal of Applied Geospatial Information, 2023)
This study area is administratively located in Parit Indah District, Bukit Raya District, Pekanbaru City, Riau Province. Geographically, the research area is located at coordinates 0° 28' 30.92" N 101° 28' 9.45" E N 0° 27' 25.63" - 101° 29' 47.30" E. The aim of this study was to find out the effect of peat soil types on subsidence. The data collection method in this study was carried out using sieve analysis, water content analysis, specific gravity, subsidence analysis, and soil testing in the laboratory. The effect of peat soil on subsidence has a significant effect between the type of peat and subsidence, the higher the maturity level of the peat, the lower the level of subsidence on peat soil. Based on the study's results, the soil consolidation test with a depth of 75cm-3m had a soil settlement value of 0.467. It is recommended to do this to reduce the impact of subsidence in the land area such as the research area so that it does not have too much impact on the construction which is carried out by hardening the location using the vertical wick drain method, as well as for building foundations it can be done using chicken claw foundation.